Xiosena: Figma-Based Prototype Design and Development for Boutique Dress Ordering Using UI/UX - Pasaribu, Indriana Febrianti; Angin, Johanes Terang Kita Perangin; Hoki, Leoni (LPPM Institut Pendidikan Nusantara Global, 2025)
Xiosena is a Figma-based prototype system created to enhance user experience in the online boutique dress ordering process. As digital commerce grows rapidly, especially within the fashion industry, seamless and aesthetically pleasing interfaces are vital to attract and retain users. This research presents the design and development of a high-fidelity prototype utilizing UI/UX principles through Figma to simulate the customer journey in ordering boutique dresses. The research methodology consisted of four main stages: requirements analysis, prototype design, usability testing with the System Usability Scale (SUS), and evaluation. The prototype emphasized clarity, ease of navigation, and appealing visuals. Results from usability testing conducted with 10 participants yielded an average SUS score of 83.5, indicating an excellent level of usability. These results validate the effectiveness of using prototyping tools in early-stage design, especially in domains requiring customized interactions like fashion e-commerce. This study contributes to the field of UI/UX development by demonstrating how prototyping with Figma can bridge the gap between user expectations and functional design in fashion-related digital platforms.